2018
DOI: 10.1016/j.jpedsurg.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Full-thickness rectal biopsy in children suspicious for Hirschsprung's disease is safe and yields a low number of insufficient biopsies

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Rectal biopsy taken under general anaesthesia 2cm above dentate line with thickness 2-3mm from the posterior aspect of rectum (2-3 biopsies taken per time), hemostasis achieved by electrocauterization and suturing the defect with previously placed traction absorbable suture. 13 All specimens fixed in 10% neutral buffered formalin were sent to Pathology Department, Faculty of Medicine, Menoufia University for routine processing and preparation of H&E staining slides for routine assessment, at least 50 sections are evaluated for the presence of ganglion cells. 9 Rectal biopsies are classified into adequate and inadequate.…”
Section: Rectal Biopsymentioning
confidence: 99%
See 1 more Smart Citation
“…Rectal biopsy taken under general anaesthesia 2cm above dentate line with thickness 2-3mm from the posterior aspect of rectum (2-3 biopsies taken per time), hemostasis achieved by electrocauterization and suturing the defect with previously placed traction absorbable suture. 13 All specimens fixed in 10% neutral buffered formalin were sent to Pathology Department, Faculty of Medicine, Menoufia University for routine processing and preparation of H&E staining slides for routine assessment, at least 50 sections are evaluated for the presence of ganglion cells. 9 Rectal biopsies are classified into adequate and inadequate.…”
Section: Rectal Biopsymentioning
confidence: 99%
“…6 Calretinin immunohistochemical stain accurately identify ganglions through staining nucleus, cytoplasm and some nerve fiber, and so it's used as additional diagnostic tool for HD. 13 Immunostaining of synaptophysin after formalin fixation may be used to identify hyperplasia of nerve fibers and stains cytoplasm of ganglion cells in non-HD specimens. It could be useful to demonstrate abnormalities of enteric innervation in rectal biopsies performed for suspected Hirschsprung's disease in the absence of acetylcholinesterase staining on frozen sections.…”
Section: Introductionmentioning
confidence: 99%
“…2 In another retrospective study of full-thickness rectal biopsies from 555 patients, aganglionosis was found in 12.1% and normoganglionosis in 87.9%. 33 In the current series, all but one normoganglionic case were managed conservatively and did well and all aganglionic cases had aganglionic rectum confirmed histopathologically after pull-through. In other words, in 2-ARL cases, normoganglionosis and aganglionosis were diagnosed with 100% accuracy with a first level biopsy and the routinely performed second level biopsy just confirmed the first level biopsy result, and in 1-ARL cases, a second level biopsy was only required to determine the type of hypoganglionosis present (Figure 4).…”
Section: Discussionmentioning
confidence: 57%
“…In present study, we did not evaluate the usefulness of the immunostaining using calretinin, S‐100, and PGP 9.5; however, these immunostainings may be reportedly recommended when concurrent AChE histochemistry and HE staining fail to prove a definitive diagnosis 20,38 . If these procedures do not confirm the definitive diagnosis, a FTB is recommended, as was performed in our TCA case 39 . If a clinical diagnosis still cannot be made, a FTB under laparotomy may ultimately be required.…”
Section: Discussionmentioning
confidence: 81%
“…20,38 If these procedures do not confirm the definitive diagnosis, a FTB is recommended, as was performed in our TCA case. 39 If a clinical diagnosis still cannot be made, a FTB under laparotomy may ultimately be required.…”
Section: Discussionmentioning
confidence: 99%